Pengembangan Panduan Konseling Behavioral Teknik Desensitisasi Sistematis Untuk Menurunkan Kecemasan dalam Belajar Siswa di sekolah menengah atas - Tia Amanda Putri; Luh Putu Sri Lestari (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This research and development uses the 4D development design (define, design, develop, disseminate) which produces a behavioral counseling guidebook product with systematic desensitization techniques to reduce anxiety in student learning. The content validity test was conducted on 3 counseling experts at the Ganesha University of Education. In the validity test using the Lawshe Formula by calculating the CVR and CVI. To measure the effectiveness using the t test which was analyzed using SPSS. The assessment instrument used in the validity test and effectiveness test is a questionnaire. Of the 17 questions used to assess content validity it was stated that the development of the guideline had very good validity. For an ES value = 2.98 which is included in the high ES category.